Twin-to-Twin Transfusion Syndrome - sharma, Deepak kumar; Garg, Eva (Journal of Nepal Paediatric Society, 2013)
TTTS is a specific condition that only occurs in multiple pregnancies of monozygotic (monochorionic) twins. When twins share a single placenta, the blood vessels become mutually interconnected in the placenta, so that blood flows back and forth between both twins. DOI: http://dx.doi.org/10.3126/jnps.v33i2.8379 J Nepal Paediatr Soc. 2013; 33(2):157